Acquisition of Cholera Within the United States - Ganesh Maniam MBA; Emily N. Nguyen MBA; John Scott Milton MD (Journal of Investigative Medicine High Impact Case Reports, 2020)
Cholera has been woven into human history through numerous pandemics, with the most recent ongoing since 1961. Global rates of cholera continue to decline, but outbreaks continue to pose diagnostic challenges for clinicians, which delays initiation of treatment and prolongs the disease course. Despite millions of infections and thousands of deaths worldwide each year, cholera remains rare in the United States, with the few cases each year usually being the result of pathogen acquisition while the patient traveled abroad. This article presents a unique case of cholera acquired in the United States, which emphasizes the necessary vigilance of symptom recognition, in the context of appropriate clinical investigation, in ensuring that the patient had a full recovery. Cholera in the United States is exceedingly rare, yet effective diagnosis with early initiation of treatment is known to reduce mortality and shorten disease course. While other more common diagnoses must definitely be excluded first, it is important for cholera to be kept on the differential for patients presenting with treatment refractory, watery diarrhea causing hypotension. This case of a patient with a recent travel history to Hawaii and infection with cholera underscores the importance of investigative medicine and clinical expertise in optimizing patient care, even when presented with rare illnesses.